The effect of halothane and pentobarbital sodium on brain ependymal cilia - O’Callaghan, Chris (BioMed Central, 2012)
BACKGROUND: The effect of anesthetic agents on ependymal ciliary function is unknown. The aim of this study was to determine the effect of halothane and pentobarbital sodium on brain ependymal ciliary function. METHODS: We used an ex vivo rat brain slice model to measure ependymal ciliary beat frequency by high speed video photography at 37°C. RESULTS: Exposure to halothane caused a significant reduction in ciliary beat frequency of 2 % (P = 0.006), 15.5 % (P < 0.001), and 21.5 % (P < 0.001) for halothane concentrations of 1.8 %, 3.4 % and 4.4 %, respectively, compared to controls. Following a one-hour wash-out period, there was no significant difference between control samples and cilia that had been exposed to 1.8 % (P = 0.5) and 3.4 % (P = 0.3) halothane. The beat frequency of cilia exposed to 4.4 % halothane had increased following the wash-out period but cilia were still beating significantly more slowly than cilia from the control group (P = <0.001). Pentobarbitone at concentrations of 25 and 50 μg/ml had no effect on ciliary beat frequency compared to controls (P = 0.6 and 0.4 respectively). A significant (P = 0.002) decrease in ciliary beat frequency was seen following incubation with a pentobarbitone concentration of 250 μg/ml (mean (SD) frequency, 24(8) Hz compared to controls, 38(9) Hz). CONCLUSIONS: Halothane reversibly inhibits the rate at which ependymal cilia beat. Pentobarbitone has no effect on ciliary activity at levels used for anesthesia. It is unclear whether the slowing of ependymal ciliary by halothane is responsible for some of the secondary central nervous system effects of volatile anesthetic agents.